Killer view: Kendra Michaels # 9 - Johansen, Roy; Johansen, Iris (New York : Grand Central Publishing, 2022)
Hired by an incarceration consultant, who prepares wealthy people for prison, to find his missing partner, army vet and former bodyguard for the rich and famous Jessie Mercado learns just how far someone will go to keep the fate of one man hidden.
new book 2023 winter.
Keywords: Private investigators -- Fiction; Murder -- Investigation -- Fiction; Missing persons -- Fiction; Suspense fiction; Detective and mystery fiction; Thriller fiction; Detective fiction; Mystery fiction